INFLUENCE OF PEER GROUP SUPERVISION ON THE NURSE PERFORMANCE IN DRUG ADMINISTRATION - Duwi Basuki; Ana Zakiyah; Windu Santoso; Isbatukhul Khoirot (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
The number of deaths and disabilities is one of them due to errors in the administration of drugs. This can be prevented with optimal supervision. The purpose of the study was to determine the influence of Peer Group Supervision on the performance of nurses in drug administration. The study sample numbered 23 implementing nurses and 23 nurse leaders. The results of observation of the performance of nurses before being given supervision training at the head of the nurse (70%) are sufficient and after being given good performance training (100%). The results of the analysis found a meaningful influence of peer group supervision on the performance of nurses (p = 0.00) by showing a positive pattern. The better the leadership supervises, the performance of nurses is also increasing. Efforts to improve nurse performance by improving peer group supervision in a planned and scheduled manner, continuous training on supervision, and socialization of Standard Operating Procedures to nurses.